2009
DOI: 10.1007/s10765-009-0656-5
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer in a Micropolar Fluid along a Non-linear Stretching Sheet with a Temperature-Dependent Viscosity and Variable Surface Temperature

Abstract: In this paper, heat transfer characteristics of a two-dimensional steady hydromagnetic natural convection flow of a micropolar fluid passed a non-linear stretching sheet taking into account the effects of a temperature-dependent viscosity and variable wall temperature are studied numerically for local similarity solutions by applying the Nachtsheim-Swigert iteration method. The results corresponding to the dimensionless temperature profiles and the local rate of heat transfer are displayed graphically for impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Since as the viscosity and thermal conductivity varies across the boundary layer, the Prandtl number also varies. The assumption of constant Prandtl number inside the boundary layer may produce unrealistic results (see Pantokratoras, 2005Pantokratoras, & 2007Rahman et al, 2009;Rahman and Eltayeb, 2011;Alam et al, 2014). Therefore the Prandtl number related to the variable viscosity and variable thermal conductivity is defined by…”
Section: Variation Of Prandtl Numbermentioning
confidence: 99%
See 2 more Smart Citations
“…Since as the viscosity and thermal conductivity varies across the boundary layer, the Prandtl number also varies. The assumption of constant Prandtl number inside the boundary layer may produce unrealistic results (see Pantokratoras, 2005Pantokratoras, & 2007Rahman et al, 2009;Rahman and Eltayeb, 2011;Alam et al, 2014). Therefore the Prandtl number related to the variable viscosity and variable thermal conductivity is defined by…”
Section: Variation Of Prandtl Numbermentioning
confidence: 99%
“…Equation (20) is the corrected non-dimensional form of the energy equation in which Prandtl number is treated as variable (see also Rahman et al, 2009;Rahman and Eltayeb, 2011;Alam et al, 2014).…”
Section: Variation Of Prandtl Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…Yasin et al 22 Dissipation of compact spirals owing to molecular viscosity close to the wall is coherent in the nonNewtonian Casson fluid flow over greater flat thermally stratified dissolving plane of a uprising paraboloid. Numerical investigations of micro-polar fluid flow over a nonlinear stretching sheet have amplified the body of cognizance on fluid flow, boundary layer analysis, and heat and mass transfer taking into account the effects of a temperature dependent viscosity 27 , MHD in the presence of Cattaneo-Christov heat flux 28 , thermo electromagnetic flow of a viscous fluid in 3D domain 29 , flow within boundary layer over an exponentially stretching surface embedded in a thermally stratified medium 30 , electrically conducting laminar fluid flow under MHD phenomenon 31 and steady natural convection flow in vertical annular micro-channel having viscosity in presence of velocity slip and temperature jump at the annular micro-channel surfaces 32 . In the recent research, Alam et al 33 concluded that thermal boundary layer would decrease with an increasing temperature dependent viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Erickson et al (1966) studied heat and mass transfer on a moving continuously moving surface. Rahman et al (2008) investigated MHD forced convective flow of a micropolar fluid past a non-linear stretching sheet with a variable viscosity and Rahman et al (2009) analyzed heat transfer in a micropolar fluid along a non-linear stretching sheet with a temperature-dependent viscosity and variable surface temperature. The magnetohydrodynamic boundary layer on a flat plate has been studied by Glauert (1961).…”
Section: Introductionmentioning
confidence: 99%